Evaluating Short-Term Climate Trends and Suitability for Tropical Urban Agriculture in Palembang and Jambi, Indonesia - Strayker Ali Muda; Benyamin Lakitan; Zulkarnain Zulkarnain; Heripan Heripan; Fitra Gustiar; Fitra Fadhilah Rizar; Fitri Ramadhani; Lya Nailatul Fadilah; Dora Fatma Nurshanti; Rofiqoh Purnama Ria (Universitas Muhammadiyah Palembang, 2025)
Climate change and food security are global challenges on this era. Climate trends play a critical role in characterizing climatic conditions and informing agricultural suitability recommendations in tropical regions. As rapidly expanding tropical urban areas, Palembang and Jambi warrant particular attention regarding to climate and food security challenges. The study aimed to evaluate climate change and suitability for urban agriculture in Palembang and Jambi. The study used secondary data of monthly rainfall, air temperature, relative humidity, and sunshine duration for the 2014-2018 and 2019-2023 periods. The collected data were subsequently averaged on a monthly basis for each observation period. Thereafter, the data were analyzed using descriptive method. The results showed that there are obvious differences of climate status between Palembang and Jambi, especially related to rainfall. Rainfall in Palembang is higher than Jambi as represented by number of wet months (5-8 months on Palembang and 3-6 months on Jambi). Meanwhile, the dry season in Jambi is potentially longer than Palembang. There was an indication of increasing air temperature in both regions, as indicated by the higher air temperature in 2019-2023 compared to 2014-2018. The air temperature increases each month in Palembang and Jambi is 1.14% and 0.93%, respectively. Nevertheless, air temperature, air humidity, and sunshine duration were still within the range of tropical plants to grow and be productive. Therefore, the recommendation of suitable cultivation in Palembang and Jambi is almost similar, in March-April and November-December applying cultivation techniques under excess water condition, otherwise in June-August on drought-resistant or minimum irrigation cultivation.